Protein requirements for maximal muscle mass and athletic performance are achieved with completely plant-based diets scaled to meet energy needs: a modeling study in professional American football players - Goldman, D. M.; Warbeck, C. B.; Karlsen, M. C. (Nutrients, 2024)
American football players consume large quantities of animal-sourced protein in adherence with traditional recommendations to maximize muscle development and athletic performance. This contrasts with dietary guidelines, which recommend reducing meat intake and increasing consumption of plant-based foods to promote health and reduce the risk of chronic disease. The capacity of completely plant-based diets to meet the nutritional needs of American football players has not been studied. This modeling study scaled dietary data from a large cohort following completely plant-based diets to meet the energy requirements of professional American football players to determine whether protein, leucine, and micronutrient needs for physical performance and health were met. The Cunningham equation was used to estimate calorie requirements. Nutrient intakes from the Adventist Health Study 2 were then scaled to this calorie level. Protein values ranged from 1.6-2.2 g/kg/day and leucine values ranged from 3.8-4.1 g/meal at each of four daily meals, therefore meeting and exceeding levels theorized to maximize muscle mass, muscle strength, and muscle protein synthesis, respectively. Plant-based diets scaled to meet the energy needs of professional American football players satisfied protein, leucine, and micronutrient requirements for muscle development and athletic performance. These findings suggest that completely plant-based diets could bridge the gap between dietary recommendations for chronic disease prevention and athletic performance in American football players.